The Eagle has Flown : A Novel - Higgins, Jack (New York Pocket Books, 1991)
German intelligence knows that Steiner survived the bungled, top-secret, assassination attempt on Winston Churchill, and is now a POW somewhere in London. Reichsfuhrer Himmler wants him back--at any cost. Racing through war-torn Europe, Himmler's top espionage unit gets closer to their target--and to the true betrayal of their mission.
Keywords: World War (1939-1945) -- Germany -- Secret service